Psychometric Properties of The Wagnild and Young Resilience Scale in Costa Rican Older Adults - Vargas Villalobos, María Auxiliadora (2024)
Purpose: To analyze the psychometric characteristics of the Wagnild and Young Resilience Scale Argentine version in a Costa Rican elderly group.Materials and methods: The study had two groups, one for the pilot study (N = 40, X = 69.38), and another for the analysis of the psychometric properties (N = 100, X = 69.31). The 25- item Wagnild and Young Resilience Scale, Argentine version, was used. An analysis by expert judgment and a pilot study were carried out to establish the scale to be validated, after which, the complete validation study was carried out. Factoranalyzes and Cronbach’s alpha were applied.Results: They were obtained two factors named: a) “selfefficacy capacity”, and b) “purpose in life capacity”. The global internal consistency was 0.84, for the first factor was 0.81 and for the second factor was 0.74.Conclusions: The scale generated is reliable and valid to assess resilience in an elderly people with similar characteristics to the present study. In the future, it is recommended to carry out qualitative analyzes to better define the constructs based on the characteristics of the population.